Historia prawa a metodologia nauk prawnych. - Plessis Du, Paul J. (Wydawnictwo Poznańskie sp. z o.o., 2010)
The paper is an attempt to answer the fundamental question whether there is any rationale behind studying Roman law for the sake of modern science and the teaching of law. In the first part of the paper, the possibility of rejecting reading Roman law as being useless from the point of view of contemporary jurisprudence is considered. It is also proposed that the current state of affairs is the result of implementation in legal history studies of R. Zimmermann’s vision that Roman law and comparative law are two useful instruments for harmonising private law. Further, a claim is made that the outcome of the discussions on the harmonisation of private law, the so-called Common Frame of Reference has been developed with no references to the accomplishments of legal history. This innovative and modern approach is then discussed and a question is asked whether it would be possible and expedient to take a fresher look at Roman law, and propose a more realistic element to jurisprudence, rejecting, at the same time, the dogmatic method, and focus, instead, on the reflection on the essence and merit of law, and the relationship between law and the environment in which it is applied. This, in the author’s opinion, should serve to make the study of Roman law more independent in relation to the current doctrine of private law. The author then concludes that Roman law may be useful for the construction of private law but only on condition that it is not reduced to an ideological banner supporting the myth of a united Europe, as the true usefulness of Roman law should be the identification of universal elements and provision of arguments to challenge the currently adopted dogmatic vision of private law.
LEGAL HISTORY AND METHODS OF JURISPRUDENCE.
Keywords: Historia prawa; Nauki prawne; Metodologia